An Optimization of Command History Search - Mateljan, Vladimir (Array, 2009)
A command that a user issues at the command prompt is a string encoded with certain character encoding. This character string can be stored into an appropriate data structure in order to be documented or reused. Additional functionality of the command line to store entered commands, along with ability to list, edit and re-execute previously entered commands, is called command history. The paper suggests an optimization of command history search based on proposed grammar of the command language.